Variation for hilum colour and its stability during four crop seasons in soybean (Glycine max) - YADAV, S P; SHARMA, S P (The Indian Journal of Agricultural Sciences, 2014)
A study was conducted during 1996-99, at New Delhi to observe the variation for hilum colour in 31 cultivars of soybean (Glycine max (L.) Merr.) in four subsequent crop seasons. Out of these 26 belonged to nucleus class and 5 tobreeder class. Except 'JS 80-21', 'Pusa 40', 'PK 327' and other cultivars with imperfect black hila, the percentage of variant hila was very low. However, the variation ranged from 0 to 50.6%. Cultivars with staunch black and brown (light-brown to dark-chocolate brown) colour hila showed stability in four seasons. Only imperfect black colour hila (also called as grey colour) showed instability of colour whenever present alone or in combination with light hila colours (creamish-buff or light-brown) masking partly the original hila colour. Appearance of few buff colour hila seeds in imperfect black hila cultivar was observed in subsequent generations of multiplication in some cultivars. Other distinguished variant problem in soybean be decided by considering three pubescence colour) along with hilum colour in varietal identification.